Vieses e lacunas no conhecimento da biodiversidade de pequenos mamíferos no Brasil - Candelária, Lana Pavão (2022)
The conversion in the land use and cover system for agriculture, pastures and expansion of cities, has modified the landscapes. The change in area size and landscape configuration transform natural habitats into anthropogenic matrices. These impacts are related to the biodiversity crisis and are intensified in the tropical region, where species diversity is greater and there are more gaps in biodiversity knowledge. The objective was to evaluate the spatial distribution of biases and knowledge gaps of small mammals in Brazil. This group is widely distributed and diverse and responds differently to human impacts. The thesis was divided into two chapters. In the first, we evaluated the biogeographic biases of articles published across Brazilian biomes, finding a bias in the quantity and density of articles for the most densely populated biomes, with the Atlantic Forest being disproportionately more researched. In the second chapter, we calculated the completeness of the inventory of small rodents in the Atlantic Forest and tested how accessibility and landscape interfere with sampling bias. The wellsampled sites were close to urban centers, roads, larger fragments and with a higher percentage of habitat coverage. We concluded the existence of a bias in the knowledge of small mammals related to population density, accessibility and large forest fragments. Although the Atlantic Forest has a greater number and density of articles, the completeness of the inventory is less than 0.03%, indicating the geographic limitation in the knowledge of the distribution of the species. We suggest calculating the completeness of the group inventory in poorly researched biomes and knowing the biases that cause the gaps. Additionally, carry out new samplings of small rodents in the Atlantic Forest in small fragments, away from roads and urban centers. These actions are necessary to accurately assess the current biodiversity crisis and improve the applicability of conservation strategies.